A Semiautomated Method for Measuring the 3-Dimensional Fabric to Renal Artery Distances to Determine Endograft Position After Endovascular Aneurysm Repair. (October 2017) - Schuurmann, Richte C. L.; Overeem, Simon P.; Ouriel, Kenneth; Slump, Cornelis H.; Jordan, William D.; Muhs, Bart E.; de Vries, Jean-Paul P. M.
Purpose: To report a methodology for 3-dimensional (3D) assessment of the stent-graft deployment accuracy after endovascular aneurysm repair (EVAR).Methods: A methodology was developed and validated to calculate the 3D distances between the endograft fabric and the renal arteries over the curve of the aorta. The shortest distance between one of the renal arteries and the fabric (SFD) and the distance from the contralateral renal artery to the fabric (CFD) were determined on the first postoperative computed tomography (CT) scan of 81 elective EVAR patients. The SFDs were subdivided into a target position (0–3 mm distal to the renal artery), high position (partially covering the renal artery), and low position (>3 mm distal to the renal artery). Data are reported as the median (interquartile range, IQR).Results: Intra- and interobserver agreements for automatic and manual calculation of the SFD and CFD were excellent (ICC >0.892, p<0.001). The median SFD was 1.4 mm (IQR −0.9, 3.0) and the median CFD was 8.0 mm (IQR 3.9, 14.2). The target position was achieved in 44%, high position in 30%, and low position in 26% of the patients. The median slope of the endograft toward the higher renal artery was 2.5° (IQR −5.5°, 13.9°).Conclusion: The novel methodology using 3D CT reconstructions enables accurate evaluation of endograft position and slope within the proximal aortic neck. In this series, only 44% of endografts were placed within the target position with regard to the lowermost renal artery.